Glutathione-the “master” antioxidant in the regulation of resistant and susceptible host-plant virus-interaction - Kozieł, Edmund; Otulak-Kozieł, Katarzyna; Rusin, Piotr (Frontiers in Plant Science, 2024)
The interaction between plant hosts and plant viruses is a very unique and complex process, relying on dynamically modulated intercellular redox states and the generation of reactive oxygen species. One of the crucial elements of ROS regulation and redox state is the production of metabolites, such as glutathione, or the activation of glutathione-associated enzymes.While the role of glutathione and specific enzymes is well understood in other types of abiotic and biotic stresses, particularly those associated with bacteria or fungi, recent advances in research have highlighted the significance of glutathione modulation and mutations in genes encoding glutathione-associated enzymes in triggering immunity or susceptibility against plant viruses. Apparently, glutathione-associated genes are involved in precisely controlling and protecting host cells from damage caused by ROS during viral infections, playing a crucial role in the host's response. In this review, we aim to outline the significant improvements made in research on plant viruses and glutathione, specifically in the context of their involvement in susceptible and resistant responses, as well as changes in the localization of glutathione. Analyses of essential glutathioneassociated enzymes in susceptible and resistant responses have demonstrated that the levels of enzymatic activity or the absence of specific enzymes can impact the spread of the virus and activate host-induced defense mechanisms. This contributes to the complex network of the plant immune system. Although investigations of glutathione during the plant-virus interplay remain a challenge, the use of novel tools and approaches to explore its role will significantly contribute to our knowledge in the field.